Interlaboratory comparison investigations (ICI) and external quality assurance schemes (EQUAS) for cadmium in urine and blood: Results from the HBM4EU project - Nübler, Stefanie; Esteban Lopez, Marta; Castano, Argelia; Mol, Hans; Schäfer, Moritz; Haji-Abbas-Zarrabi, Karin; Bury, Daniel; Koch, Holger M.; Vaccher, Vincent; Antignac, Jean-Philippe; Dvorakova, Darina; Hajslova, Jana; et al. (International Journal of Hygiene and Environmental Health, 2021)
Human biomonitoring (HBM) of cadmium is essential to assess and prevent toxic exposure. Generally, low cadmium levels in urine and blood of the general population place particularly high demands on quality assurance and control measures (QA/QC) for cadmium determination. One of the aims of the HBM4EU project is to harmonize and advance HBM in Europe. Cadmium is one of the chemicals selected as a priority substance for HBM implementation in the 30 European countries under HBM4EU. For this purpose, analytical comparability and accuracy of the analytical laboratories of participating countries was investigated in a QA/QC programme comprising interlaboratory comparison investigations (ICI) and external quality assurance schemes (EQUAS). This paper presents the evaluation process and discusses the results of four ICI/EQUAS rounds for the determination of cadmium in urine and blood. The majority of the 43 participating laboratories achieved satisfactory results, although low limits of quantification were required to quantify Cd concentrations at general population exposure levels. The relative standard deviation of the participants? results obtained from all ICI and EQUAS runs ranged from 8 to 36% for cadmium in urine and 8?28% for cadmium in blood. Applying inductively-coupled plasma mass spectrometry (ICP-MS), using an internal standard, and eliminating molybdenum oxide interferences was favourable for the accurate determination of cadmium in urine and blood. Furthermore, the analysis of cadmium in urine was found to have a critical point at approximately 0.05 ?g/l, below which variability increased and laboratory proficiency decreased. This QA/QC programme succeeded in establishing a network of laboratories with high analytical comparability and accuracy for the analysis of cadmium across 20 European countries.
CRIS-Team WoS Importer:2021-06-04